Highly porous single-phase rhombohedral CrxRh2−xO3 nanofibers expediting oxygen evolution reaction - Taehui Kwon; Kyungmin Kim; Sampath Prabhakaran; Subin Choi; Jiwon Kim; Yeji Yim; Jihyun Park; Hoi Ri Moon; Myung Hwa Kim; Do Hwan Kim; Youngmi Lee (Applied Surface Science Advances)
Single-phase rhombohedral CrxRh2−xO3 nanofibers are demonstrated as an excellent and stable electrocatalyst for oxygen evolution reaction (OER) under alkaline condition. Facile optimization of the annealing temperature for electrospun nanofibers composed of Cr/Rh metal precursors and poly(vinylpyrrolidone) could produce highly porous nanofibers of single-phase CrxRh2−xO3 by randomly distributing two metal ions of Cr3+ and Rh3+ in the rhombohedral crystalline lattice sites. Single-phase CrxRh2−xO3 could then induce the best synergistic effect of Cr and Rh owing to the perturbation of the surface electronic structure of the electrocatalyst active site and much enlarged electroactive surface area. Density functional theory (DFT) simulation integrated with experimental data indicated that the increased activity was due to moderate d-band center energy levels. This regulates oxygen desorption and adsorption capacities in the intermediates (*OH, *O, and *OOH). Conclusively, CrxRh2−xO3 nanofibers exhibited superior OER catalytic performances (low overpotential and Tafel slope with high stability and easy product desorption) compared to other Rh-related catalysts reported to date.